2015
DOI: 10.1002/jcph.574
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal exposure to H2blockers and to proton pump inhibitors and asthma development in offspring

Abstract: Fetal exposure to H2 blockers (H2 Bs) or proton pump inhibitors (PPIs) has been reported to be associated with asthma in children. We evaluated the risk of asthma in offspring following prenatal H2 Bs. We enrolled 91 428 children and their mothers who resided in southern Israel during 1998-2011. The computerized medications database was linked with records from the district hospital. Of the eligible children, 11 227 developed asthma, and overall 5.5% had been exposed to H2 Bs or PPIs prenatally. The risk of de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 28 publications
0
16
0
Order By: Relevance
“…The study did not address GERD and may be confounding the association. Yitshak-Sade et al 14 The main possible bias in the study was confounding by indication, which was supported by a statistically signifi cant association between maternal consumption of the medications 2 y after delivery and childhood asthma. Residual confounding factors associated with asthma could exist in their databases.…”
Section: Identifi Cation Of Relevant Studiesmentioning
confidence: 81%
See 4 more Smart Citations
“…The study did not address GERD and may be confounding the association. Yitshak-Sade et al 14 The main possible bias in the study was confounding by indication, which was supported by a statistically signifi cant association between maternal consumption of the medications 2 y after delivery and childhood asthma. Residual confounding factors associated with asthma could exist in their databases.…”
Section: Identifi Cation Of Relevant Studiesmentioning
confidence: 81%
“…We further assessed heterogeneity by using the sensitivity analyses and removing each study from the analysis to assess the changes in the I 2 values and determine which studies contributed most significantly to the heterogeneity. The number of patients in the study by Hak et al 16 was lower compared with other studies, and Yitshak-Sade et al 14 investigated the use of H 2 RA or PPIs rather than the use of any acid-suppressive drug. We found that when the studies by Yitshak-Sade et al 14 and Hak et al 16 were removed, the I 2 values decreased from 88% to 0% (P = .68), but the effect remained significant (RR = 1.45; 95% CI 1.35-1.56; P < .00001; Fig 3).…”
Section: Overall Use Of Acid-suppressive Drugs During Pregnancy and Tmentioning
confidence: 88%
See 3 more Smart Citations